Chess and the conscious mind: Why Dreyfus and McDowell got it wrong. (30th August 2018) - Montero, Barbara Gail
Abstract : Is it possible to deliberate consciously during a 1‐min‐per‐player chess game? I argue that, in contrast to views of the philosophers Hubert Dreyfus and John McDowell, even 1‐min‐per‐player chess games involve conscious thought and deliberation. In making my case, I rely on experimental results from two small‐scale studies I conducted on chess players, chess players' first‐person reports, and theoretical considerations that distinguish automatic skills from consciously controlled skills. This work bolsters Yu‐Hsuan Chang and David Lane's 2016 study suggesting that simultaneous chess exhibitions and speed chess allow time for calculation. It also aims to inspire future, larger‐scale studies investigating the role of declarative thought in 1‐min‐per‐player games.